1972
DOI: 10.1002/hlca.19720550732
|View full text |Cite
|
Sign up to set email alerts
|

Weitere Bufadienolide aus Ch'an Su. Über Krötengifte, 39. Mitteilung

Abstract: From the toad venom Ch'an Su the bufadienolides 1, 4, 9, 10, 12, 15, 17, 20, 22, 25 and 18, the latter as diacetate 19 were isolated and their structure elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1972
1972
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 22 publications
(1 reference statement)
0
6
0
Order By: Relevance
“…Bufadienolides are considered the main active constituents of toad venom, [ 10–35 ] such as bufalin, cinobufagin, arenobufagin, and resibufogenin, which exhibit anticancer activities in a variety of cancers. Bufadienolides are a type of C‐24 steroids with cardiotonic activities and originally isolated from the traditional Chinese medicine toad venom, and they have been used for the treatment of heart disease in traditional remedies as well as in modern medicinal therapy with potent anticancer activities.…”
Section: The Active Constituents Of Toad Venommentioning
confidence: 99%
“…Bufadienolides are considered the main active constituents of toad venom, [ 10–35 ] such as bufalin, cinobufagin, arenobufagin, and resibufogenin, which exhibit anticancer activities in a variety of cancers. Bufadienolides are a type of C‐24 steroids with cardiotonic activities and originally isolated from the traditional Chinese medicine toad venom, and they have been used for the treatment of heart disease in traditional remedies as well as in modern medicinal therapy with potent anticancer activities.…”
Section: The Active Constituents Of Toad Venommentioning
confidence: 99%
“…It was found that these cardenolides originated from the plants on which the larvae of butterflies fed. 116 However, for the fireflies, 77,78 Cinobufagin 3-glutaryl--arginine ester 89 Cinobufagin hemisuberate 81 Cinobufagin 3-pimeloyl--arginine ester 77,78 Cinobufagin 3-suberoyl--arginine ester 77,78 (cinobufotoxin) Cinobufagin 3-succinoyl--arginine ester 77,78 Cinobufagin 3-sulfate 90 Cinobufaginol 91 64 Cinobufotalin 92 65 Cinobufotalin 3-suberoyl--arginine ester 77,78 (cinobufotalitoxin) Desacetylcinobufagin 3-hemisuccinate 77 Desacetylcinobufagin 3-succinyl--arginine 90 16-Desacetylcinobufaginol 93 Desacetylcinobufotalin 94 16-Desacetyl-19-oxocinobufotalin 93 11 ,19-Dihydroxytelocinobufagin 95 20,21-Epoxyresibufagin 96 Gamabufotalin 97 59 Gamabufotalin 3-adipoyl--arginine ester 77,98 Gamabufotalin hemisuberoate 77 Gamabufotalin 3-pimeloyl--arginine ester 77,82 Gamabufotalin 3-suberoyl--arginine ester 77,99 (gamabufotalitoxin) Gamabufotalin 3-succinoyl--arginine ester 77,98 Gamabufotalin 3-sulfate 77 Gamabufotaliniol 100 60 Hellebrigenin 46 10 Hellebrigenin 3-suberoyl--arginine ester (hellebritoxin) 101 4 -Hydroxybufalin 93 15-Hydroxybufalin 93 19-Hydroxybufalin 93 19-Hydroxybufalin 3-suberoyl--histidine ester 86 19-Hydroxybufalin 3-suberoyl--3-methylhistidine ester 86 12 -Hydroxycinobufagin 93 19-Hydroxycinobufotalin 93…”
Section: Photinus (Fireflies)mentioning
confidence: 99%
“…succinoyl--arginine ester77 Resibufogenin 3-suberoyl--arginine ester112 (resibufotoxin) Telocinobufagin94 71 Telocinobufagin 3-glutaryl--arginine ester103 Telocinobufagin 3-suberoyl--arginine ester104 (telocinobufotoxin) Telocinobufagin 3-suberoyl--glutamine ester106 …”
mentioning
confidence: 99%
“…Compounds 1 and 2 had unusual 7/5/6/5 and 5/7/6/5 ring systems, respectively, instead of the 6/6/6/5 skeleton presented in common bufadienolides, which interested us to presume the biogenetic pathway among these compounds. Cinobufotalin ( 6 ), 19‐hydroxylcinobufotalin ( 5 ) and 19‐oxocinobufotalin ( 4 ) were three known ingredients of toad venom 15. The aldehyde group at C‐10 in 4 should be formed by oxidation of the corresponding hydroxymethyl group in 5 , which was an oxide of 6 , as the formation of resibufagin and hellebrigenin 5.…”
Section: Methodsmentioning
confidence: 99%